Online Religion and Religion Online: Reform Judaism and Web-Based Communication - Frost, Jonathon K. (Journal of media and religion, 2014)
This study examines the online communication practices of American congregations associated with the Union for Reform Judaism (URJ), the governing body of American and Canadian Reform congregations, through a content analysis of 252 American URJ congregational Web sites. Web site content was grouped into two categories, "religion online" and "online religion." Religion online content promotes the organization and provides organizational information, including information related to organizational identity building, community outreach, and encouraging civic and social action. Online religion content allows the user to engage in spiritual activity via the Internet (Helland, 2000; Farrell, 2011). ANOVA and MANOVA analyses were used to determine significant differences in content based on congregation size. Results revealed larger congregations were more likely to use Web sites for organizational identity building, mobilization of civic and social action, and the practice of "online religion," lending support to the existence of a size-based digital divide among URJ congregations.